Insult and Humiliation as Language and Law Phenomena - A. N. Baranov; L. A. Erokhina (Теория и практика судебной экспертизы, 2020)
The differences between legal and shared understanding of insult and humiliation are discussed. Legislator defines “insult” as a type of humiliation expressed in an indecent form, which assumes that humiliation is a generic category (more general) and insult is a specific category (a case of the generic category). Albeit, there is no definition for “humiliation” in the law. It is shown that in the Russian literary language the meanings of the words “insult” and “humiliation” do not come down to genus-species relation, which in some cases results in legal collisions. The article provides of collocations for the words “insult” and “humiliation” (as well as the corresponding verbs and other forms of the same family of words) given, pointing at essential semantic differences between them, which makes it impossible to consider these forms as implementation of genus-species relation. In particular, the agential contexts, reflexive’s contexts, of verbal and non-verbal action, of verbal action effect and other. It is shown that the concept of social status, which is often associated with the category of “humiliation” in scientific works, in fact, is not a necessary feature of humiliation acts. The judicial practice on cases of insult, which is under the apparent impact of the difference between legal and shared understanding of the words and conceptual categories in question, is given.